How is the Emotional Intelligence and Personality of Students in Following the Learning Process? - Tambaip, Beatus; Riyanto, Pulung; Rediani, Ni Nyoman; Syahruddin (LPPM Undiksha, 2022)
Success in the student learning process cannot be separated from emotional intelligence and personality, that's why a study that aims to analyze the emotional intelligence and personality of PGSD students is carried out. The type of research used is descriptive qualitative. The sample of this research is 100 students. The data collection method used is a questionnaire. The questionnaire used consists of 54 terminals that have been tested for validity. Data analysis in the study was carried out interactively with 3 techniques, namely data reduction, data presentation and drawing conclusions. The results showed that emotional intelligence was in the good category, this was indicated by the results of research students answered that the condition of emotional intelligence was good. However, there are two statements that need to be considered, namely the dimension of being able to control anger better. As for the personality of PGSD students, it shows that students are more likely to approach extrovent personalities, students prefer to interact with other people rather than be alone, but there are still some students who prefer to be silent rather than answer questions or prefer to convey. results. discuss compared to what he did. This condition is supported by the results of observations made in class. Where some students show that they lack confidence in expressing their opinions in practice or in conveying the results of discussions.